2004
DOI: 10.1387/ijdb.041894cs
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of lens induction in chicken embryos: in vitro studies of early tissue interactions

Abstract: Early studies on lens induction suggested that the optic vesicle, the precursor of the retina, was the primary inducer of the lens; however, more recent experiments with amphibians establish an important role for earlier inductive interactions between anterior neural plate and adjacent presumptive lens ectoderm in lens formation. We report here experiments assessing key inductive interactions in chicken embryos to see if features of amphibian systems are conserved in birds. We first examined the issue of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 62 publications
2
38
0
2
Order By: Relevance
“…There are a number of other data from multiple species that show the repression of lens fate outside of the future lens primordium (see Donner et al, 2006b). In the most recent work using chickens, Grainger and co-workers have shown that close contact between the optic vesicle and the prospective lens surface ectoderm prevents the infiltration of neural crest cells (Sullivan et al, 2004). Earlier studies in the mouse have shown that mesenchymal cells are present between the optic vesicle and surface ectoderm and only after the contact between these structures is established is the lens placode formed (Furuta and Hogan, 1998).…”
Section: Formation Of the Neural Tube Optic Vesicles And Lens Progenmentioning
confidence: 99%
“…There are a number of other data from multiple species that show the repression of lens fate outside of the future lens primordium (see Donner et al, 2006b). In the most recent work using chickens, Grainger and co-workers have shown that close contact between the optic vesicle and the prospective lens surface ectoderm prevents the infiltration of neural crest cells (Sullivan et al, 2004). Earlier studies in the mouse have shown that mesenchymal cells are present between the optic vesicle and surface ectoderm and only after the contact between these structures is established is the lens placode formed (Furuta and Hogan, 1998).…”
Section: Formation Of the Neural Tube Optic Vesicles And Lens Progenmentioning
confidence: 99%
“…We find that presumptive olfactory placode ectoderm is specified to express Pax6 and Dlx3 by HH8 (Bailey et al, 2006) (this paper). Neuronal specification begins around HH10-11, implying that ectoderm has seen signals that will direct its fate even before it is morphologically visible as a placode, analogous to trigeminal, otic and lens placode specification (Baker et al, 1999;Groves and Bronner-Fraser, 2000;Sullivan et al, 2004).…”
Section: Induction Is Complete Before Placodal Morphogenesismentioning
confidence: 99%
“…Consistent with this, cranial ectoderm expresses epibranchial placode markers in response to BMP7 from pharyngeal endoderm but trunk ectoderm does not do so (Begbie et al, 1999). Competence to form lens is also restricted to lateral and ventral head ectoderm in amphibians and aves (Jacobson, 1966;Sullivan et al, 2004). In Amblystoma punctatum, as in chick, competence to form olfactory placode extends, at early stages, over a wide area of head ectoderm, but not to anterior flank ectoderm after stage 15 (Haggis, 1956).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These correspond to a period of lens-forming competence (Servetnick and Grainger, 1991) in the mid/late gastrula ectoderm, the acquisition of a lens-forming bias throughout the head ectoderm during neurulation (Grainger et al, 1997), specification of lens cell fate towards the end of neurulation, and differentiation, an aspect of lens development which continues throughout life (Grainger, 1992). While the definition of these stages are described in more detail in another chapter of this volume (Sullivan et al, 2004) it is worth noting that one of the current challenges is to mesh the embryological and molecular genetic definitions of lens induction.…”
Section: Lens Induction Is a Multi-step Processmentioning
confidence: 99%